PERILAKU PROSOSIAL REMAJA PADA SISWA SMA ATAU SEDERAJAT YANG MENGIKUTI KEGIATAN EKSTRAKURIKULER - Siti Fatonatul Arifah; Handrix Chris Haryanto (Universitas Paramadina, 2018)
This research aims to describe about Adolescents’s Prosocial Behavior on High School Students Whose joining Extracuricular Activities. Respondent of this research were High School Students Whose joining Extracuricular Activities. The number of respondents in this research were 210 respondents. Convenience sampling technique is used to sample the population. The measuring instrument in this research was Revise Prosocial Tendencies Measure (R-PTM) from Carlo and Randall (2002). There was 22 items in the questionnaire, and there was open question about respondents perceived benefit of Extracuricular Activities. The results showed that the majority of Prosocial Behavior in low categories. Extracuricular that was having the highest mean was pramuka. The most perceived benefit was training cooperation.